Adaptasi Ekofisiologi Terhadap Iklim Tropis Kering: Studi Anatomi Daun Dua Puluh Jenis Tumbuhan Berkayu - Nurul Fahida; Zia Ulhak; Nur Arafah; Dwi Saraswati; Erni Suryani (Jompa Research and Development, 2024)
The research carried out is useful for knowing the shape of the leaves, types, distribution areas of the plants, as well as the local and ethnic names of twenty types of woody plant leaves that are 5 to 10 years old. This research was carried out at the Sadundu Pidu Rora waterfall, Bima Regency. Based on the research results, there were 20 types of leaves that were studied and had different leaf shapes and sizes from other leaves, the leaves studied had local names from the Bima area and had different types and distribution areas. Using the free roaming method and carrying out an approach analysis of plant types that are appropriate to the tropical climate conditions found in the Sadundu Pidu waterfall area in Rora and schematized with clear names for each plant examined as well as documentation of each woody plant leaf.